German family study on hereditary breast-ovarian cancer. Issue 8 (August 1996) - Hamann, U; Becher, H; Zimmermann, T; Pella, K; Bastert, G; Chang-Claude, J
Abstract : An estimated 5% to 10% of all breast and ovarian cancers are attributed to dominant susceptibility genes. Two such genes, BRCA1 and BRCA2, were recently identified. The involvement of these genes was studied in 43 German breast only and breast-ovarian cancer families. All families contained three or more cases of breast or ovarian cancer, with at least two diagnosed under the age of 60 years. Multipoint linkage analysis gave a maximum lod score of 2.13 at the BRCA1 locus under the assumption of genetic heterogeneity, with an estimated 50% of families being linked. Among the 33 breast only cancer and 10 breast-ovarian cancer families, the estimated proportions of linked families were 35% and 75%, respectively. Sixteen families with at least four cases of female breast cancer diagnosed under the age of 60 years, or male breast cancer diagnosed at any age, were analysed for linkage to BRCA2. Positive lod scores at BRCA2 were obtained in six families.